2015
DOI: 10.5935/0004-2749.20150037
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of matrix metalloproteinases-1 and -9 and opioid growth factor in rabbit cornea after lamellar keratectomy and treatment with 1% nalbuphine

Abstract: Purposes: To evaluate the effects of nalbuphine 1% on the expression of metalloproteinase 1 (MMP-1), metalloproteinase 9 (MMP-9), and opioid growth factor (OGF) in rabbit corneas after lamellar keratectomy. Methods: The rabbits were assigned to two groups: group nalbuphine (GN, n=30), which received 30 μL of nalbuphine 1% in 4 daily applications at regular intervals until corneal epithelialization, and group control (GC, n=30), which received physiological saline solution under the same conditions adopted in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…On the other hand, group V showed a significant increase compared to the control group. This came in accordance with the work of other researchers in which MMP-1 and MMP-9 were detected in the basal membrane and superficial stroma after lamellar keratectomy [35] . The authors reported that the overexpression of MMP-1 and MMP-9 occurred in corneal ulcers and led to a rapid degradation of corneal extracellular matrix.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, group V showed a significant increase compared to the control group. This came in accordance with the work of other researchers in which MMP-1 and MMP-9 were detected in the basal membrane and superficial stroma after lamellar keratectomy [35] . The authors reported that the overexpression of MMP-1 and MMP-9 occurred in corneal ulcers and led to a rapid degradation of corneal extracellular matrix.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, MMP-9 might be an important enhancing factor for inflammation preventing re-epithelialization of the cornea following thermal injury. However, the mechanism is still not well understood [33,34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…34 Table 1 represents the association of inflammatory cytokines with CP. [35][36][37][38][39][40][41][42][43][44][45][46][47][48] Some studies reported that immune abnormalities have a strong relationship with CP and erythropoietin (EPO) plays a neuroprotective role in cell injuries associated with CP. EPO is a glycoprotein containing 165 amino acids, and is known as pleiotropic cytokine.…”
Section: Implications Of Cytokine Dysregulations In Cpmentioning
confidence: 99%
“…Lu et al 45 and Silva et al 46 IFN-γ (interferon gamma) Key role in brain trauma and degenerative diseases. Implicated in the pathogenesis of PVL, causes upregulation of the major histocompatibility complexes (I and II) and CD cell surface markers.…”
mentioning
confidence: 99%
“…This phenomenon can be provoked by an uncontrolled increase in MMP-9 activity in the tear and this protease is associated with severe signs of inflammation. Therefore, MMP-9 is an interesting therapeutic target and pharmacological modifiers of MMP-9 expression have been seen to have differing degrees of success in modifying its activity in vivo [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. MMP-9 is implicated in a range of pathologies, including DED [ 21 ], ocular surface injury [ 22 ], microbial keratitis [ 23 ], corneal ulceration [ 24 ], corneal neovascularization [ 25 ], keratoconus [ 26 , 27 ] and SS [ 28 ].…”
Section: Introductionmentioning
confidence: 99%